2014
DOI: 10.1016/j.cell.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Map of Human T Cell Compartmentalization and Maintenance over Decades of Life

Abstract: SUMMARY Mechanisms for human memory T cell differentiation and maintenance have largely been inferred from studies of peripheral blood, though the majority of T cells are found in lymphoid and mucosal sites. We present here a multidimensional, quantitative analysis of human T cell compartmentalization and maintenance over six decades of life in blood, lymphoid and mucosal tissues obtained from 56 individual organ donors. Our results reveal that the distribution and tissue residence of naïve, central and effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
568
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(644 citation statements)
references
References 43 publications
57
568
1
2
Order By: Relevance
“…In contrast to the decline in cervix, we found that the percentage of TRMs increase in endometrial tissues of postmenopausal compared to premenopausal women and that this increase remains stable with postmenopausal aging. These findings were unexpected, since previous reports indicated no changes in TRM frequency with aging in other tissues, including the lung and intestines (Thome et al., 2014). Our findings suggest that differential mechanisms control the presence and the induction of TRMs in the FRT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the decline in cervix, we found that the percentage of TRMs increase in endometrial tissues of postmenopausal compared to premenopausal women and that this increase remains stable with postmenopausal aging. These findings were unexpected, since previous reports indicated no changes in TRM frequency with aging in other tissues, including the lung and intestines (Thome et al., 2014). Our findings suggest that differential mechanisms control the presence and the induction of TRMs in the FRT.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, memory T cells with TRM characteristics have been identified at multiple mucosal surfaces including the lung, the intestines, and the FRT (Thome & Farber, 2015; Thome et al., 2014). In the FRT, more than 95% of T cells are effector memory (Saba et al., 2010; Yeaman et al., 1997), with a high proportion of T cells expressing CD103 in the vagina, endocervix (CX), ectocervix (ECX), and endometrium (EM) (Duluc et al., 2013; Moylan et al., 2016; Rodriguez‐Garcia et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Trm cells have been found in multiple organs, with elegant studies from Farber and colleagues tracking memory T‐cells in individuals of various ages. Human and mouse Trm cells share many characteristics, including CD69 expression and reduced expression of S1P receptor 1 37, 38. Similarly, CD4 Trm cells in skin are, like their mouse equivalent, mainly found in the dermis 39.…”
Section: Memory Cd4 T‐cells Are Found Throughout the Bodymentioning
confidence: 99%
“…-effector memory CD4 + and CD8 + T cells within the lymphoid compartments, including blood, accumulate rapidly with age (12). These high frequencies of heterologous memory T cells, if donor reactive, are postulated to play key roles in belataceptresistant rejection in both clinically sensitized as well as nonsensitized recipients.…”
Section: Ccr7mentioning
confidence: 99%